write a polynomial function f of least degree that has the rational coefficients, a leading coefficient of 1, and the given zeros. Given zeros: -2,2,-1,3, sqrt 11

(x+2)(x-2)(x+1)(x-3) takes care of the integer roots.

Now, if √11 is a root, then (x-√11) is a factor, but that leaves a dangling √11, which will show up in the coefficients. So, you also need to include (x+√11), since

(x-√11)(x+√11) = x^2-121, which has rational coefficients.

So, the final polynomial is

f(x) = (x+2)(x-2)(x+1)(x-3)(x-√11)(x+√11)

and yu can expand that out if you like.

oops. (x-√11)(x+√11) = x^2-11

To find the polynomial function, we will use the fact that if a zero is given as \(x = a\), then \(x-a\) is a factor of the polynomial.

Given zeros: -2, 2, -1, 3, √11

Since all the zeros are rational, they will come in pairs like (-2, 2), (-1, 1), and (√11, -√11).

Therefore, the factors of the polynomial function can be written as follows:

\(x - (-2) = x + 2\)
\(x - 2\)
\(x - (-1) = x + 1\)
\(x - 3\)
\(x - \sqrt{11}\)
\(x + \sqrt{11}\)

Now, to find the polynomial function, we multiply all the factors together:

\(f(x) = (x + 2)(x - 2)(x + 1)(x - 3)(x - \sqrt{11})(x + \sqrt{11})\)

Expanding this expression, we get:

\(f(x) = (x^2 - 4)(x^2 - 1)(x^2 - 11)\)

Multiplying further, we get:

\(f(x) = (x^2 - 4x^2 + 4)(x^2 - 11)\)

Simplifying, we get:

\(f(x) = (1 - 3x^2)(x^2 - 11)\)

Expanding again, we get:

\(f(x) = x^4 - 11x^2 - 3x^2 + 33x^2\)

Simplifying further, we get:

\(f(x) = x^4 + 20x^2\)

So, the polynomial function \(f(x)\) of least degree with the given zeros is \(f(x) = x^4 + 20x^2\).

To write a polynomial function with the given zeros, we need to use the fact that if a number, say "a", is a zero of a polynomial function, then (x - a) is a factor of that function.

Given zeros: -2, 2, -1, 3, sqrt(11)

Let's start by writing the factors corresponding to the given zeros:

(x - (-2)) = (x + 2)
(x - 2)
(x - (-1)) = (x + 1)
(x - 3)
(x - sqrt(11))

Now, we'll multiply these factors together to get a polynomial function of least degree:

f(x) = (x + 2)(x - 2)(x + 1)(x - 3)(x - sqrt(11))

Next, we can simplify this expression by expanding the product:

f(x) = (x^2 + 2x - 2x - 4)(x + 1)(x - 3)(x - sqrt(11))
= (x^2 - 4)(x + 1)(x - 3)(x - sqrt(11))

Finally, we can multiply the remaining factors together:

f(x) = (x^2 - 4)(x^2 - 2x - 3x + 3 - sqrt(11)x + sqrt(11)3)
= (x^2 - 4)(x^2 - 5x + 3 - sqrt(11)x + 3sqrt(11))

Expanding this further is possible, but based on the given instructions, we have satisfied the conditions of having rational coefficients, a leading coefficient of 1, and the given zeros with the polynomial function:

f(x) = (x^2 - 4)(x^2 - 5x + 3 - sqrt(11)x + 3sqrt(11))